2023
DOI: 10.1002/adma.202212272
|View full text |Cite
|
Sign up to set email alerts
|

PIP2 Alteration Caused by Elastic Modulus and Tropism of Electrospun Scaffolds Facilitates Altered BMSCs Proliferation and Differentiation

Abstract: engineering and stem cell therapy. [3][4][5] There is increasing evidence that biomaterial surface topography is an essential factor that selectively influences cell adhesion and, in some cases, promotes cell differentiation. [6] To date, various biomaterials with different topographies at both the micrometer and nanometer scales, such as columns, grooves, and submicron fibers, have been applied to study the influence of topography on cellular functions. [7] Electrospun submicron fibers have been extensively e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…Reproduced with permission. [ 108 ] Copyright 2023, Wiley‐VCH GmbH. b) Schematic diagram of the effect of matrix elasticity on the differentiation of MSCs.…”
Section: Impact Of Mechanical Signalsmentioning
confidence: 99%
See 2 more Smart Citations
“…Reproduced with permission. [ 108 ] Copyright 2023, Wiley‐VCH GmbH. b) Schematic diagram of the effect of matrix elasticity on the differentiation of MSCs.…”
Section: Impact Of Mechanical Signalsmentioning
confidence: 99%
“…It was reported that the overexpression of BCL‐6 and/or the inhibition of miR‐126a‐5p promoted the expression of PIP5k‐PIP2 pathway and thus stimulated the proliferation and differentiation of stem cells (Figure 4a). [ 108 ] Overall, the mechanism of how stiffness regulates the osteogenic differentiation of stem cells is still not clear, and further research is needed.…”
Section: Impact Of Mechanical Signalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to previous work, 62 this paper presents advancements in the manufacturing technology of soft robots, enabling the reversible and programmable functionality of a single-layer hydrogel robot. Besides, if combined with flexible sensing, 63 multi-physical cooperative driving, 64,65 and therapeutic capabilities, 66,67 the single-layer hydrogel robot could realize the integration of diagnosis and treatment and environmental monitoring in the biomedical field. For instance, the integration of temperature-responsive color changes could potentially enable the realization of an unconstrained environmental monitoring system and locally driven soft robot systems.…”
Section: Response Principle Of the Single-layer Hydrogel Robotmentioning
confidence: 99%
“…The contractile force of actin stress fibers in the cytoskeleton appears to be essential in regulating cell adhesion, shape, and even differentiation. In a study by Gao et al, 30 the use of different elastic matrices regulated the differences in gene expression of bone marrow mesenchymal stem cells (BMSCs). Different research groups have attempted to study the force exerted by cells on the underlying substrate.…”
Section: Tsc Adhesion and Morphologymentioning
confidence: 99%